Inaplicabilidad del art. 42 de la ley orgánica de comunicación en relación al libre ejercicio de la comunicación en el Ecuador - NAZAMUES HERRERA, WILLIAM EDISON (2016)
Undoubtedly, the interest premium professional future of law in this study, which seeks to identify the main shortcomings and limitations of the aforementioned regulations and which is in force since June 25, 2013; The law in question has inserted us in a complex process of socialization and discussion between different media and different sectors of the national community, omitting that before approval was criticized, questions and observations of a different nature; You can not argue that Act Communication has generated social problems resulting from excesses in the performance of the Superintendency of Information and Communication is the technical watchdog, auditing, intervention and control, impose penalties, which has broad powers to enforce the rules of regulation of Information and Communication; Just between the contradictions that I believe exist between this law and the Constitution evident obvious limitations to the fundamental right of people to express themselves, communicate and think freely, I will look at the analysis of art. 42 of the law and then transcribe as the starting point for this process of study and analysis. The problem is generated by the failure of that statute and its contradiction with the constitutional regulations have also cited, this is verified by the permanent insults to journalists, critics, analysts, panelists taking a different view of public policies formulated by the current government have expressed their views and arguments in public and private media; It is also verified by the permanent harassment allegations and actions directed from the public or state communication, recurrent sanctions as biased by the Superintendency of Information and Communication; these are the reasons why I consider regulatory alternatives should be generated to the Communications Act, evidencing a real fulfillment of constitutional principles and international treaties for decades have advocated the inviolability of freedom of expression, information and communication.